Finding the needle in the haystack: the diagnostic accuracy of the faecal immunochemical test for colorectal cancer in younger symptomatic patients - D'Souza,N; Monahan,K; Benton,SC; Wilde,L; Abulafi,M (Colorectal Disease, 2021)
AimDetection of early onset colorectal cancer is challenging, and remains a rare diagnosis amongst younger people with gastrointestinal symptoms. We investigated whether faecal immunochemical testing (FIT) could identify younger patients at higher risk of colorectal cancer or serious bowel disease including colorectal cancer, inflammatory bowel disease or advanced adenomas.MethodsA subgroup analysis was performed of symptomatic patients under 50 years of age (<50) from the NICE FIT study, a multicentre, prospective diagnostic accuracy study of FIT conducted between October 2017 and December 2019. The diagnostic accuracy of FIT for colorectal cancer and serious bowel disease was investigated in younger patients at different faecal haemoglobin (f-Hb) cut-offs of 2, 10 and 150 µg blood/g faeces (µg/g).ResultsEarly onset colorectal cancer was diagnosed in 1.5% (16/1103) of younger symptomatic patients. The sensitivity of FIT for younger patients aged <50 was 87.5% (95% CI 61.7%–98.4%), 81.3% (54.4%–96.0%) and 68.8% (41.3%–89.0%) at f-Hb cut-offs of 2, 10 and 150 µg/g, respectively. The positive predictive value for colorectal cancer increased from 4.2% (2.3%–6.9%) to 11.5% (5.9%–19.6%) at cut-offs of 2 and 150 µg/g, while the positive predictive value for serious bowel disease increased from 31.3% (26.3%–36.5%) to 65.6% (55.2%–75.0%) at the same cut-offs. The negative predictive value of FIT for colorectal cancer remained above 99.5% at all cut-offs.ConclusionDetectable f-Hb on FIT in symptomatic younger patients may indicate referral for investigation of colorectal cancer and serious bowel disease.